Effect of Rotation Speed and Powder Bed Volume on Powder Flowability Measured by a Powder Rheometer: Evaluation of the Humidity Effect on Lactose Powder Flowability - Takamasa Mori; Kanaho Sakurada; Kenta Kitamura (ChemEngineering, 2025)
Relative humidity during storage is known to affect powder flowability, although its effect on powder flowability remains unclear. Various techniques have been used to evaluate powder flowability, including measurement of the rotational torque of the powder bed, which is a novel method. However, studies investigating the effect of relative humidity on powder flowability using rotational torque measurements are limited. Therefore, this study aimed to examine the influence of relative humidity during storage on the flowability of lactose powder through rotational torque measurement of the powder bed using an Anton Paar powder rheometer. Rotation speed had a minimal effect, except when the powder was stored at a high relative humidity of 99%. The effect of relative humidity was more pronounced at a smaller powder volume (30 mL) than that at the other volumes tested. Of the techniques employed, including the angle of repose and bulk density measurements, the rotational torque measurement of the powder rheometer exhibited the highest sensitivity to variations in relative humidity. It was also found that the measured rotation torque hardly changed when the rotation speed was below a critical value, indicating that the optimal rotation speed exists to measure the representative rotation torque of each powder.